The New Quantum Technologies Demand New World Vision (Global Journal of Science Frontier Research, 2025)
Year 2025 is announced to be International Year of Quantum Science and Technology and let s face it the new Quantum Technologies require revision of our old world vision Researchers found that surfaces of metamaterials can bend focus and transformlaser beams and serve as beam shapers And an electron excited with energy h when passing between the column surfaces of metamaterials can spontaneously transition to a lower energy level with energy h 1 h Classical optic cannot explain such spontaneous transitions and the researchers working with metamaterials are trying to explain it with resonance with the vacuum field Vacuum cannot have resonance frequencies because there is nothing in the vacuum to vibrate And here it becomes clear that our old belief that ether does not exist it is vacuum does not fit the new quantum research I came to the conclusion that Space Matrix NEMF must exist from my life-long studies of the aura which is weak NEMF Since only nonlinear fields do not dissipate and can imprint information I concluded that the Universe must have been created from nonlinear electromagnetic field NEMF
Keywords: quantum technologies; metamaterials; ether NEMF; metamaterials’ NEMF